Effects of caffeine, sodium bicarbonate, and their combined ingestion on high-intensity cycling performance - Kilding, A. E.; Overton, C.; Gleave, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
To determine the effects of ingesting caffeine (CAFF) and sodium bicarbonate (SB), taken individually and simultaneously, on 3-km cycling time-trial (TT) performance. Method: Ten well-trained cyclists, age 24.2 ± 5.4 yr, participated in this acute-treatment, double-blind, crossover study that involved four 3-km cycling TTs performed on separate days. Before each TT, participants ingested either 3 mg/kg body mass (BM) of CAFF, 0.3 g · kg-1 · BM-1 of SB, a combination of the two (CAFF+SB), or a placebo (PLAC). They completed each 3-km TT on a laboratory-based cycle ergometer, during which physiological, perceptual, and performance measurements were determined. For statistical analysis, the minimal worthwhile difference was considered ~1% based on previous research. Results: Pretrial pH and HCO3 were higher in SB and CAFF+SB than in the CAFF and PLAC trials. Differences across treatments for perceived exertion and gastric discomfort were mostly unclear. Compared with PLAC, mean power output during the 3-km TT was higher in CAFF, SB, and CAFF+SB trials (2.4%, 2.6%, 2.7% respectively), resulting in faster performance times (-0.9, -1.2, -1.2% respectively). Effect sizes for all trials were small (0.21-0.24). Conclusions: When ingested individually, both CAFF and SB enhance high-intensity cycling TT performance in trained cyclists. However, the ergogenic effect of these 2 popular supplements was not additive, bringing into question the efficacy of coingesting the 2 supplements before short-duration high-intensity exercise. In this study there were no negative effects of combining CAFF and SB, 2 relatively inexpensive and safe supplements.